Exploring said nursi’s methodology in the study of Christianity - Shehu, Fatmir Mehdi (2017)
This study attempts to investigate Said Nursi’s methodology in the study of Christianity. The goal of this research is to explore Nursi’s approach in dealing with Christianity in light of his major work entitled Risale-i Nur. His views on Christianity as expressed by him in his master piece will be examined in order to determine his methodology. This paper starts with a brief introduction on Nursi’s life and work followed by a discussion on his methodology used by him in the study of Christianity. Selected statements of Said Nursi on Christianity are cited from his Risale and supported by other related sources, and then, are analysed in order to identify, classify and interpret his methodology moderately. Descriptive and analytical methods will be employed in the entire study. The findings of this research will add to the discipline of modern comparative religion the insights of the original work of a Muslim thinker in the study of Christianity.